Modeling and optimization of geothermal heat exchanger performance under Sub-Saharan climate region - Algeria - - Lebbihiat, Nacer (Universty Of El-oued جامعة الوادي, 2024)
The ground air heat exchanger (GAHE) geothermal system is commonly used to exploit clean and renewable energy for cooling and heating buildings. In this study, literature review on the geothermal energy practices and technologies in Algeria and around the globe has been conducted. Thus, countermeasures and solutions to promote the development and utilization of geothermal energy in the country are addressed. Furthermore, according to the literature the helical configuration of GAHE requires a limited ground space and lesser trench length for installing long pipes. Therefore, thermal performance of helical ground air heat exchanger (HGAHE) has been experimentally analyzed under Saharan climate conditions during summer season. A flexible PVC pipe with a diameter of 0.06 m and a length of 30 m has been arranged as a helical-coil layout to design the HGAHE and it is inserted into a borehole of 5 m depth. Besides, a transient numerical model has been developed and validated against the experimental data to investigate the heat penetration into the borehole. Moreover, the numerical model has also been employed to investigate the impact of different important operating and geometric parameters. The experimental finding acknowledged that, thermal performance derating factor (TPDF) increments with increasing the operation time and air velocity. After 3 hours of operation time, the highest TPDF is attained as 0.27 with a velocity of 20 m s-1, whereas the lowest TPDF is observed as 0.14 for a velocity of 10 m s-1. Numerical results revealed that, the borehole temperature distribution in the radial direction decreases rapidly with the distance away from the pipe surface. In addition, the parametric study indicated that, the helical diameter, inlet temperature and ventilation velocity are the most effective parameters, whereas the pipe diameter and pitch size have a moderate impact on thermal performance of the HGAHE system. Furthermore, increasing the thermal effusivity of backfill material can enhance the heat exchange rate and effectiveness of the system. Along with the numerical results, multiple regression method has been used to propose effective model to predict thermal behavior of the HGAHE system. نظام التبادل الحراري هواء أرض (GAHE) المعروف أيضًا بنظام الطاقة الجيوحرارية يستخدم بشكل شائع لاستغلال الطاقة النظيفة والمتجددة لتبريد وتدفئة المباني. في هذه الدراسة، تم إجراء إستعراض للمراجع حول ممارسات وتقنيات الطاقة الجيوحرارية في الجزائر وحول العالم. وبالتالي، تم التطرق إلى التدابير والحلول لتعزيز تطوير واستخدام الطاقة الجيوحرارية في البلاد. علاوة على ذلك، وفقًا للمراجع، فإن الشكل اللولبي لنظام GAHE يتطلب مساحة أرض محدودة وطول خندق أقل لتثبيت الأنابيب الطويلة. لذلك، تم تحليل الأداء الحراري لنظام التبادل الحراري هواء أرض اللولبي (HGAHE) تجريبيًا تحت ظروف المناخ الصحراوي خلال فصل الصيف. تم ترتيب أنبوب PVC مرن بقطر 0.06 متر وطول 30 متر على شكل لفائف لتصميم HGAHE وتم إدخاله في بئر بعمق 5 أمتار. بالإضافة إلى ذلك، تم تطوير نموذج عددي إعتمادا على البيانات التجريبية لفحص إنتشار الحرارة في البئر. علاوة على ذلك، تم استخدام النموذج العددي أيضًا للتحقيق في تأثير مختلف العوامل التشغيلية والهندسية الهامة. تشير النتائج التجريبية إلى أن معامل تقليل الأداء الحراري (TPDF) يزيد مع زيادة وقت التشغيل وسرعة الهواء. بعد 3 ساعات من وقت التشغيل، تم الحصول على أعلى TPDF بواقع 0.27 مع سرعة 20 مترًا في الثانية، في حين يُلاحظ أدنى TPDF تم الحصول عليه هو 0.14 بسرعة 10 مترًا في الثانية. كشفت النتائج العددية عن أن توزيع حرارة البئر في الاتجاه الشعاعي ينخفض بسرعة مع البعد عن سطح الأنبوب. بالإضافة إلى ذلك، أشارت الدراسة الإحصائية إلى أن القطر اللولبي ودرجة الحرارة الداخلة وسرعة الهواء هي العوامل الأكثر فعالية، في حين أن قطر الأنبوب والمسافة بين لفتين له تأثير معتدل على الأداء الحراري لنظام HGAHE. وعلاوة على ذلك، يمكن زيادة الفاعلية الحرارية لمواد التعبئة الخلفية لتعزيز معدل تبادل الحرارة وفعالية النظام. جنبًا إلى جنب مع النتائج العددية، تم استخدام طريقة الانحدار المتعدد لاقتراح نموذج فعال لتنبؤ السلوك الحراري لنظام HGAHE.
أطروحة دكتوراه تخصص الطاقات في الميكانيك في العلوم التكنولوجيا
Keywords: * Geothermal energy; Heat exchange rate; Effectiveness; CFD; HGAHE system; Saharan climate.; الطاقة الجيوحرارية، معدل تبادل الحرارة، الفاعلية، ديناميكا الموائع العددية، نظام HGAHE، مناخ صحراوي.